MAKNA MEDITASI VIPASSANĀ BAGI MAHASISWA SEKOLAH TINGGI AGAMA BUDDHA SYAILENDRA - Setyadi, Danang; Kustiani, Kustiani; Sukodoyo, Sukodoyo (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2020)
This research is about the meaning of vipassanā meditation for Syailendra Buddhist College’s students. The background of STAB Syailendra students before I started the lesson always do meditation. It is certainly influential in everyday life in the midst of advances in technology that carries a negative influence on students. Based on this it is important to conduct research to know the meaning and application of meditation vipassanā as a recombination material for students and STAB Syailendra Institution for further meditation implementation. This research uses qualitative methods of descriptive. The subject of this study is student and lecturer STAB Syailendra. The techniques and data collection instruments used are using observation techniques, interviews, and documentation. Data collection instruments using interview guidelines, observation guidelines and a camera or recording device. How to guarantee the validity of data obtained through continuous observation, triangulation, member check. The data obtained is analyzed using the Miles & Hurberman method which includes data collection, data reduction, data presentation, and draw conclusions or verification. The results of this study include the meaning and application of meditation vipassanā is to increase attention, increase alertness, improve discipline, increase awareness, increase calmness, control emotions, control themselves, Improve concentration, increase memory, practice mindset, courage in making decisions, be polite, run the Syllamore well. Furthermore, more attention to lecturers when giving material, realizing when doing everything, focus on what is done in everyday life, pleasing, having contemplation, can think clearly, neatly arranged, peaceful, Do not humble themselves, more self-mastered.